Electrically reconfigurable metamaterial absorber operating in C band - Le Van Long; Bui Son Tung; Bui Xuan Khuyen; Bui Huu Nguyen; Vu Dinh Lam (Journal of Military Science and Technology, 2023)
Reconfigurable metamaterial absorbers have garnered significant attention due to their ability to actively manipulate absorption characteristics without modifying the underlying geometrical structure. This study proposes a straightforward approach for the creation of electrically reconfigurable metamaterial absorbers through the integration of varactor diodes. The presented work encompasses two distinct types of absorbers: single-band and dual-band metamaterial absorbers. By leveraging an external voltage, effective control over absorption frequencies in the C-band is achieved. The underlying principle is elucidated, wherein controlled variations of effective parameters within the integrated diode facilitate the adjustment of the magnetic resonance frequency of the metamaterial absorber. Consequently, our research might contribute to the advancement of efficient, dynamic, and adaptive metamaterial-based devices endowed with enhanced functionalities for diverse applications in the realms of telecommunications, electromagnetic shielding, and beyond.